Fluid-induced transition from banded kyanite- to bimineralic eclogite and implications for the evolution of cratons. (15th June 2017) - Sommer, H.; Jacob, D.E.; Stern, R.A.; Petts, D.; Mattey, D.P.; Pearson, D.G.
Abstract: Heterogeneous, modally banded kyanite-bearing and bimineralic eclogites from the lithospheric mantle, collected at the Roberts Victor Diamond mine (South Africa), show a reaction texture in which kyanite is consumed. Geothermobarometric calculations using measured mineral compositions in Perple_X allowed the construction of a P-T path showing a steep, cool prograde metamorphic gradient of 2 °C/km to reach peak conditions of 5.8 GPa and 890 °C for the kyanite eclogite. The kyanite-out reaction formed bimineralic eclogite and is probably an integral part of the mineralogical evolution of most archetypal bimineralic eclogites at Roberts Victor and potentially elsewhere. The kyanite-out reaction occured at close to peak pressure (5.3 GPa) and was associated with a rise in temperature to 1380 °C. Mass balance calculations show that upon breakdown, the kyanite component is fully accommodated in garnet and omphacite via a reaction system with low water fugacity that required restricted fluid influx from metasomatic sources. The δ 18 O values of garnets are consistently higher than normal mantle values. Each sample has its characteristic trend of δ 18 O variance between garnets in the kyanite-bearing sections and those in the bimineralic parts covering a range between 5.1‰ and 6.8‰. No systematic change in O-isotope signature exists across the sample population. Differences in garnet trace element signatures between differing lithologies in the eclogites are significant. Grossular-rich garnets coexisting with kyanite have strong positive Eu-anomalies and low Gd/Yb ratios, while more pyrope-rich garnets in the bimineralic sections have lost their positive Eu-anomaly, have higher Gd/Yb ratios and generally higher heavy rare earth element contents. Garnets in the original kyanite-bearing portions thus reflect the provenance of the rocks as metamorphosed gabbros/troctolites. The kyanite-out reaction was most likely triggered by a heating event in the subcratonic lithosphere. As kyanite contains around 100 ppm of H2 O it is suggested that the kyanite-out reaction, once initiated by heating and restricted metasomatic influx, was promoted by the release of water contained in the kyanite. The steep (high-P low-T) prograde P-T path defining rapid compression at low heating rates is atypical for subduction transport of eclogites into the lithospheric mantle. Such a trajectory is best explained in a model where strong lateral compression forces eclogites downward to higher pressures, supporting models of cratonic lithosphere formation by lateral collision and compression.